Quantum physics, illusion or reality? - Rae, Alastair I. M. (Cambridge University Press, 2004)
Einstein's famous remark that 'God does not play dice' was his response to a set of new scientific ideas now known as quantum physics. This revised edition to Alastair Rae's introductory exploration into this area contains a new chapter covering theories developed during the past fifteen years.